Patient one - Goldberg, Leonard S. (Goldberg, Leonard S. Ballineau/Ross medical thriller series., 2012)
U.S. President John Merrill is hosting Russian President Dimitri Suslev at a glittering state dinner to celebrate a new economic pact. As the after-dinner toasts begin, the two leaders, their wives, and scores of prominent guests become violently ill. Merrill and Suslev, along with the other stricken guests, are rushed to the nearest hospital. As Secret Service agents struggle to secure the hospital and locate Merrill's daughter, the President's personal physician -- who's been withholding critical medial information about the Commander-in- Chief -- tries desperately to stabilize the President.